Pelatihan Dasar Atletik Pada Guru Pendidikan Jasmani Se-Kota Bandar Lampung Tahun 2021 - Dwi Priyono; Ardian Cahyadi; Sudirman Husin; Heru Sulistianta (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
The science of sports coaching is the study of sports training problems, physical, mental, nutrition, refereeing, competition and scoring problems, in order to achieve sports goals. The purpose of this service proposal is to provide information, understanding, knowledge, and skills through training activities, and participate in developing competence in the field of sports, especially in athletics. The method that will be used in this service uses a guided practice approach based on scientific studies in the field of sports. After carrying out this training, it can be concluded that the training participants were assisted in refreshing the basic athletic training for physical education teachers. So that teachers understand the basic rules and management of basic training in athletics.